Endogenous Leverage and Advantageous Selection in Credit Markets - Nenov, Plamen T. (Review of Financial Studies, 2017)
I study asset price amplification in an asymmetric information model. Entrepreneurs issue debt to finance investments in a physical asset. They have private information about their success probabilities. For a given debt level, higher asset prices require entrepreneurs to invest more of their own funds. This makes bad entrepreneurs more reluctant to mimic good ones; as a result, good entrepreneurs increase their equilibrium leverage and invest more, and this amplifies the initial asset price increase. This model generates predictions about the credit market that are qualitatively consistent with existing evidence.